Combined channel estimation and data decoding based on fuzzy logic - Young-Bae Byun; Takama, Y.; Hirota, K. (IEEE transactions on instrumentation and measurement, 2002)
A simple method that detects the data sequence and at the same time estimates the channel condition is proposed using the Viterbi algorithm and fuzzy logic for the convolutional code. After a fixed number of decoding steps, the fuzzy logic unit reads the branch metric value of the survivor and the difference between maximum and minimum survivor path metric values at the Viterbi decoder and estimates the channel condition with the signal-to-noise ratio. The proposed method enables the channel estimation regardless of what kinds of modulator and demodulator are used. In the experiment, constraint length 7 and code rate 1/2 convolutional code that is standardized by the European Space Agency (ESA) is used. The effective movement range of the proposed channel estimation method is from 0.0 dB to 25 dB.